Decision Support System for Alternative Selection of Family Medicinal Plants using the WEB-Based TOPSIS Method - Nurasima Wahid; Dwi Arief Prambudi; Nurlaila (Politeknik Pertanian Negeri Samarinda, 2020)
Indonesia is a growing place for 80 percent of medicinal plants in the world with 28,000 plant species are grown and 1,000 species of which have been used as medicinal plants. The utilization of plant raw materials is still fixed by one type of material even though these materials can be used by various types of diseases. Family Medicinal Plants, known as